Cycling vs running - Walters, J. (1999)
Within a complete training program there are many types of training activities such as imitations, skating, weights, calisthenics, games and, of course, running and cycling. Since running and cycling form the base for much of the aerobic training, the question often arises as to which is better, cycling or running. Personally, author believes that both running and cycling play an important role in the total aerobic training program and would, therefore, recommend that both methods of training be used. The following may, perhaps, be helpful to decide when cycle or run. 7 Considerations for aerobic cycling and 8 considerations for aerobic running. Since there are pros and cons for both aerobic running and cycling, author usually suggests that in looking at the total combination of aerobic training that 30% of this total is running, 30% cycling and the remaining 40% is up to the skater`s preference.